Kolaborasi dalam Skenario Pelembagaan Sosial (SPS) atau Social Institution Scenario (SIS) Permukiman Sempadan Sungai - Muhammad Agus Syukron; Wahyudi Wahyudi (Departement of Mathematics Education, 2022)
Environmental experts and social experts have a dilemmatic view of responding to communities inhabiting river border settlements, that the risk of degradation land resources, disasters and safety to river border settlers, in others has an optimistic view that increasing the capacity and proficiency of land resources will bring the community closer to environmental functions and services, so that it will be able to increase the level of community welfare. This study examines the process of structuring the social interaction of community elements residing on the border of the Brantas River